2017
DOI: 10.1097/scs.0000000000003827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Suturation Plus Surgicel Application on Post-Tonsillectomy Bleeding and Pain

Abstract: Suturation plus Surgicel application increased pain levels while decreasing bleeding incidence during the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Most of our participants stated that they utilised both of these methods during the procedure. A number of different extra measures to prevent secondary post-tonsillectomy bleeding have been described in the literature, including suturing the faucial pillars together 3 , 10 . However, the benefits of these measures are controversial 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of our participants stated that they utilised both of these methods during the procedure. A number of different extra measures to prevent secondary post-tonsillectomy bleeding have been described in the literature, including suturing the faucial pillars together 3 , 10 . However, the benefits of these measures are controversial 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The study qualities ranged between 4 and 9, that is, overall moderate or high quality (Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] 3.3 | Primary outcome…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Not cost efficient. Too expansive for some surgical units [58]Y TachoSil [48]Y Evarrest® [54]N TachoCombGelatin-based HemostatGelatin-Thrombin Hemostatic Matrix (GTHM)Y [67]NY [61], [67]N [68]Case study by reviewing 42 pediatric patients and retrospective data analysis [61], randomized, controlled trial in adults [68, 69] and children [67, 70] and a review [71]Floseal™ Hemostatic MatrixPost-op [61, 71]simple, safe, and efficacious and cost-effective [61, 70]Y [72]Absorbable cellulose-based Hemostatoxidized cellulose polymer hemostatic agentY [73]Y (when combine with suturation) [74]N (when combine with suturation) [74]Surgicel plus saturation on total of 760 patients (393 males, 367 females) between the ages of 4 and 35 years [74]Surgicel®, Cellistypt®, Pahacel®, Oxycel®, Gelita®, GuraTamp®Intra-opaids in clot formation by activation of the extrinsic and intrinsic coagulation pathways,Introduced a risk of aspiration and suffocation [75]; Possible inflammation [76]. Y Surgicel® [77]N for othersBismuth subgallate-basedBSG- adrenaline paste, BSG- phenylephrine hydrochloride mixtureY [78]Y (BSG mixed with phenylephrine hydrochloride) [79]Y BSG with adrenaline for primary PTH [80], N for secondary PTH [81]N [81]Clinical study on patients underwent tonsillectomy [78, 81]Spectrum Chemical (powder), mixing 26 g of BSG powder to 20 ml of normal saline with 0.7 ml of 1:1000 adrenalinePost-opdecreases operating time by significantly reducing the hemostasis time and the number of ligatures [78, 81]; accelerates the cascade of blood clotting [79]; accelerate the intrinsic clotting pathway through the activation of factor XII (Hageman factor) [82].…”
Section: Main Text: Topical Biomaterials Used For Pthmentioning
confidence: 99%
“…A review of topical hemostatic agents in 2010 found that Surgicel had been used in otolaryngologic procedures, such as mastoid and endonasal surgeries [60]. For tonsillectomy, Surgicel application plus suturing decreases PTH rates [74].…”
Section: Main Text: Topical Biomaterials Used For Pthmentioning
confidence: 99%
See 1 more Smart Citation